The effect of dynamic local self-preheating in laser cladding on grey cast iron - Yi, Peng (Strojniški vestnik, 2015)
In laser cladding, high cooling rates are accompanied by superior mechanical and metallurgical properties. However, these characteristics, along with the additive nature of the process, significantly contribute to the formation of thermal stresses, which are the main cause of any potential delamination and crack formation across the remelted area. To reduce thermal stress and better manage the microstructure, a strategy of dynamic local self-preheating has been designed. Laser-cladding experiments with no preheating, static global preheating, and dynamic local preheating with grey cast iron have been conducted. Parallel to the experimental investigations, numerical models have been established in order to study the temperature distributions and thermal stresses in different processes. The results indicate that dynamic local self-preheating contributes to reducing the transient thermal stress and residual stress compared with other methods. With self-preheating of the substrate, microstructures of the coarse-grained region are well-developed. The self-preheated sample reveals a more compact structure in the fusion area and can exhibit less cracking during the cladding process.
Keywords: lasersko navarjanje; lokalno predgrevanje; mikrostruktura; numerični modeli; siva litina